Abnormalities in grey matter structure in embouchure dystonia. (August 2019) - Mantel, Tobias; Altenmüller, Eckart; Li, Yong; Meindl, Tobias; Jochim, Angela; Lee, André; Zimmer, Claus; Dresel, Christian; Haslinger, Bernhard
Abstract: Introduction: Embouchure dystonia (ED) is a debilitating movement disorder in professional brass players leading to involuntary muscle contractions/spasms during play. To date, activity changes in sensorimotor cortices during motor tasks and tactile processing, as well as connectivity changes at rest in sensorimotor and auditory brain networks have been described in the disease. Objective: To characterize differences in grey matter volume and asymmetry between brass musicians suffering from ED, healthy brass musicians and healthy nonmusicians. Methods: High-resolution structural magnetic resonance imaging was obtained from 24 brass musicians with ED, 23 healthy brass musicians and 24 healthy nonmusicians. Whole-brain voxel-wise morphometry and asymmetry analyses, as well as region-of-interest-based volumetry analysis were performed on the subjects' images and compared between groups. Further, correlations with clinical parameters were investigated. Results: ED patients showed increased grey matter volume in the primary sensorimotor cortex in relation to both healthy brass players and nonmusicians. Both healthy and diseased musicians showed increased thalamic symmetry in relation to nonmusicians; diseased brass musicians additionally showed increased basal ganglia symmetry compared to nonmusicians. There was an inverse correlation of disease duration with both mean putaminal volume and the extent of basal ganglia asymmetry. Conclusion: This work provides first evidence for structural abnormalities in task-specific orofacial (musician's) dystonia. Somatotopy-related structural primary sensorimotor cortex changes underlying previously observed functional abnormalities underscore the role of maladaptive plasticity in the disease. The study further shows subcortical brain (a)symmetry changes in healthy brass players and hints at a possible role of such changes in focal dystonia. Highlights: Primary sensorimotor grey matter volume is increased in embouchure dystonia. Structural changes are observed both compared to brass professionals and nonmusicians. Brass musicians show increased thalamic symmetry compared to nonmusians In embouchure dystonia subcortical symmetry changes extend to the basal ganglia. Disease duration associates with subcortical volume reduction and symmetry increase.